MONITORING OF CALCIUM CONTENT OF RAW COW MILK - Ye. S. Kandinskaya; S. V. Redkin; G. V. Chebakova (Ветеринария сегодня)
Milk is a natural food product that is unique in its nutritive value and signifcance for human organism. Its composition is balanced in major biochemical components as well as mineral components including calcium. Calcium is essential for many metabolic processes and is contained in milk in easily digestible and phosphorus-balanced form. Therefore, decrease in its content in milk creates prerequisites for insufcient meeting the body need in the said microelement and has an eﬀect on human metabolism especially in children. Results of laboratory testing of 400 milk samples collected from clinically healthy Holstein and Black and White Spotted cows kept on 40 farms located in the Moscow Oblast in 2001–2017 are presented. The raw milk was examined for the following quality indicators: sensory, physical and chemical as well as microbiological parameters. It was found that calcium concentration in milk depended on the season. It was shown that the majority of tested milk samples did not comply with the veterinary and sanitary quality parameters despite of the tendency to increase in analyzed parameter content in autumn. The monitoring showed recent decrease in calcium content of cow milk and dairy products intended for infant food. Average calcium content of raw milk was found to be 900–950 mg; it varied from 700 up to 1,100 mg of calcium/litre of milk. Further testing scheme based on analysis of such factors as pure protein, diet, biologically active dietary supplements is proposed. Such testing will allow comprehensive assessment of exogenous factors inﬂuencing calcium content of milk as well as harmonization of Russian requirements for food quality and safety assessment with the European ones.